Whole-genome Sequencing for Surveillance of Invasive Pneumococcal Diseases in Ontario, Canada: Rapid Prediction of Genotype, Antibiotic Resistance and Characterization of Emerging Serotype 22F - Deng, Xianding; Memari, Nader; Teatero, Sarah; Athey, Taryn; Isabel, Marc; Mazzulli, Tony; Fittipaldi, Nahuel; Gubbay, Jonathan B. (Frontiers in Microbiology, 2016)
Background. Molecular typing is essential for inferring genetic relatedness between bacterial pathogens. In this study, we applied whole genome sequencing (WGS) for rapid prediction of sequence type and antibiotic resistance for invasive pneumococcal isolates. Methods. 240 isolates from adults (≥ 50 years old) in Ontario, Canada during 2009 to 2013 were subjected to WGS. Sequence type, antibiotic susceptibility and resistance were predicted directly from short reads. Emerging non-vaccine serotype 22F was further characterized by WGS. Results. Sequence type was successfully determined for 98.3% of isolates. The overall sensitivity and specificity for antibiotic resistance prediction were 95% and 100% respectively, compared to standard susceptibility testing methods. WGS-based phylogeny divided emerging 22F (ST433) strains into two distinct clades: clade A harboring a 23kb-prophage and anti-phage PhD/Doc system and clade B with virulence-related proteases. Five isolates in clade A developed macrolide resistance via 5.1kb mega element recombination (encoding mefE and msrD), while one isolate in clade B displayed quinolone resistance via a gyrA mutation. Conclusions. WGS is valuable for routine surveillance of pneumococcal clinical isolates and facilitates prediction of genotype and antibiotic resistance. The emergence of 22F in Ontario in the post-vaccine era and evidence of evolution and divergence of the 22F population warrants heightened pneumococcal molecular surveillance.